The impact of the Strategy to Nominate ideas on the working Memory and Learn to perform the skills of sending and receiving the volleyball for the students (Journal of the College of Basic Education, 2024)
The research aimed to prepare educational exercises and employ them with the strategy of filtering thoughts to learn to perform the skills of sending and receiving in volleyball for female students, and to identify the effect of the strategy of filtering thoughts on working memory and the performance of learning the skills of sending and receiving in volleyball for female students. The experimental approach was adopted by designing the experimental and control groups, while the limits of the community were represented by female students. Fifth Preparatory School of Sama Al-Tafawq Preparatory School for girls for the academic year (2023/2024), numbering (62) students, naturally distributed into two divisions, (A) and (B), from which the research sample was randomly selected to reach (50), with a percentage of (80.645%). From this population, then one of them was chosen in a simple random way to be the experimental group from Division (A) and the other from Division (B) as a control group with an equal number of students from both divisions (25), and the remaining number from the two divisions (12) female students was chosen for the sample of the exploratory experiment, and they are They represent 19.355% of their community of origin. Educational ages were prepared and employed in the vocabulary of the strategy under research and then experimenting for a period of (8) weeks at the rate of one lesson per week, as the research experience began with the application of tribal skill tests by its perception of each of the players of the research groups on Sunday corresponding to the date (4/3/2024) And then apply these educational exercises with the strategy of filtering ideas for the students of the experimental group, while the control group applies the exercises followed as they are for the period from Monday corresponding to the date (5/3/2024) until Sunday, corresponding to the date (25/4/2024), and finishing from This experiment is to apply the dimensional tests on Tuesday, corresponding to the date (26/4/2024), and the results were addressed with the SPSS system to be extracts and applications. So, the conclusions and applications are that preparing educational exercises using the strategy of filtering ideas in practical lessons in volleyball is appropriate for fifth-grade middle school students, and helps in improving the level of working memory in volleyball, and in improving learning to perform the transmission and reception skills in volleyball among the female students who learn it, and with superiority over the female students who learn it. Without it, it is necessary when preparing educational exercises for the idea filtering strategy that there is a space of freedom to think and stimulate the mind and body to complete the educational tasks, taking into account the improvement of working memory as the mental factor supporting this skill performance.